Exegetical Phrase 'Keep Working On Your Salvation' According To Philippians 2:12 - Apiyusu La"ia; Widi Prasetyo; Connie Laurina (Theological Journal Kerugma, 2022)
Considering the influence of teaching in God's churches as well as writings on salvation are still contradictory, the writer must immediately write this paper with enthusiasm and joy. Anxiety occurs when among believers themselves still adhere to two to three understandings of salvation. First, there are those who argue that salvation is entirely from God and there is no human contribution in doing it. Because humans are sinners and do not have any reason for doing salvation. Second, there are those who argue that salvation is done by humans, God is only the provider. And the result is that many think that man will lose his salvation if he is not sincere in working for his salvation. Third, there are those who argue that salvation in Philippians 2:12 is a collaboration between God and man. God works and man must also work. Some of the focus problems above can produce good and bad qualities. Because there are some people who claim to believe but do not work out their salvation, but live as they please because they believe that the sins of the past, present and future sins of the Lord Jesus have been completed. Philippians 2:12 will consistently explore the true meaning, whether it is really God who works one hundred percent without human contribution or humans who have to work on salvation and God is the only provider.